2020
DOI: 10.1097/gox.0000000000003158
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Poly-4-hydroxybutyrate Mesh in Ventral Hernia Repair: A Systematic Review and Pooled Analysis

Abstract: Background: Within the past decade, poly-4-hydroxybutyrate (P4HB) biosynthetic mesh has been introduced as a potential alternative to traditional biologic and synthetic mesh in ventral hernia repair (VHR). The aim of this study was to systematically assess clinical outcomes with the P4HB in VHR. Methods: A literature search identified all articles published in 2000 involving the use of P4HB in VHR. Descriptive statistics were used to synthesize collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…14,[39][40][41] Poly-4-hydroxybutyrate monofilament biosynthetic mesh in clean or contaminated VHR appears a reliable and cost-effective long-term alternative to biological or non-absorbable synthetic mesh, but its use is still being evaluated. 42 A synchronous hernia mesh repair should not be contraindicated during other intra-abdominal operations (appendicectomy, cholecystectomy, small bowel resection). 8,9,11 An extraperitoneal mesh repair (retrorectus or onlay) rather than intraperitoneal mesh repair is preferable in contaminated VHR, emergency VHR, emergency laparotomy or with concurrent colorectal surgery.…”
Section: Absorbable Vs Permanent Meshmentioning
confidence: 99%
“…14,[39][40][41] Poly-4-hydroxybutyrate monofilament biosynthetic mesh in clean or contaminated VHR appears a reliable and cost-effective long-term alternative to biological or non-absorbable synthetic mesh, but its use is still being evaluated. 42 A synchronous hernia mesh repair should not be contraindicated during other intra-abdominal operations (appendicectomy, cholecystectomy, small bowel resection). 8,9,11 An extraperitoneal mesh repair (retrorectus or onlay) rather than intraperitoneal mesh repair is preferable in contaminated VHR, emergency VHR, emergency laparotomy or with concurrent colorectal surgery.…”
Section: Absorbable Vs Permanent Meshmentioning
confidence: 99%
“…For the current study, we produced our own absorbable electrospun P4HB scaffolds. P4HB was chosen as knitted P4HB implants have shown promise in reconstructive surgery for ventral hernia repair and in our preclinical studies for pelvic floor repair. ,,, In addition, electrospun P4HB for other applications such as a dural or dermal , substitution are encouraging, but the available studies are limited, and no studies on electrospun P4HB for pelvic floor repair have been conducted. Because fibroblasts are the main cell type of the connective tissue of the vaginal wall and are responsible for maintaining the ECM, , their function is critical in assessing implant performance in the pelvic floor and to predict how the implant will interact with the host.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have reported outcomes associated with P4HB mesh with a variety of hernia repair techniques and patient populations. 5 - 14 The majority of these studies have reported medium-term outcomes in the range of 18 to 36 months. 5 - 13 The current study is uniquely designed to evaluate clinical outcomes of P4HB mesh along a continuum of early, intermediate, and long-term timeframes.…”
mentioning
confidence: 99%